KEWAJIBAN ORANG TUA TERHADAP NAFKAH ANAK PASCA-BALIGH: TELAAH FIQH DAN RELEVANSINYA DI ERA MODERN - Bagus Jamroji (Institut Agama Islam Hasanuddin Pare, 2024)
This study examines parental obligations to provide financial support for children post-puberty from the perspective of Islamic jurisprudence (fiqh) and its relevance in the modern era. Using a descriptive-analytical approach based on literature review, the study analyzes Quranic verses, prophetic traditions, and interpretations from various Islamic schools of thought. The findings indicate that financial obligations do not automatically cease when a child reaches puberty, particularly if they are not yet financially independent. For example, the Shafi'i school considers the obligation valid until the child becomes mature and self-reliant, while the Hanafi school generally limits it to the age of puberty. In the modern context, socio-economic challenges such as extended education and delayed financial independence make post-puberty financial support highly relevant. The maqashid syariah framework, which emphasizes child welfare, strongly supports the flexibility of this obligation. Key challenges include low compliance levels, particularly among divorced parents, necessitating stronger policies and public awareness efforts. The study concludes that integrating legal, moral, and educational approaches can effectively support post-puberty financial obligations while fostering harmonious and empowered Muslim families in the modern era.